Direct Cardiac Actions of Sodium Glucose Cotransporter 2 Inhibitors Target Pathogenic Mechanisms Underlying Heart Failure in Diabetic Patients - Uthman, Laween; Baartscheer, Antonius; Schumacher, Cees A.; Fiolet, Jan W. T.; Kuschma, Marius C.; Hollmann, Markus W.; Coronel, Ruben; Weber, Nina C.; Zuurbier, Coert J. (Frontiers in Physiology, 2018)
Sodium glucose cotransporter 2 inhibitors (SGLT2i) are the first antidiabetic compounds that effectively reduce heart failure hospitalization and cardiovascular death in type 2 diabetics. SGLT2i were designed to decrease serum glucose levels by inhibiting SGLT2 in the kidney and to induce glycosuria. Direct off-target cardiac actions of SGLT2i have recently been documented. Here, we review the effects of SGLT2i on the various cardiac cell types and on cardiac function, and discuss how these may contribute to the cardiovascular benefits observed in large clinical trials. SGLT2i impaired the Na+/H+ exchanger (NHE-1) and reduced cytosolic [Ca2+] and [Na+] in cardiomyocytes. In addition, Empagliflozin (Empa), one of the best studied SGLT2i, increased myocardial mitochondrial calcium. Empa also maintained cell viability and ATP content following hypoxia/reoxygenation in cardiomyocytes and endothelial cells. Hyperglycemia-induced eNOS reduction was alleviated by Empa in human umbilical vein endothelial cells (HUVEC), and a different SGLT2i Dapagliflozin (Dapa) improved vasorelaxation in hyperglycemic and TNF-α stimulated aortic rings. Attenuation of vascular dysfunction by Empa, Dapa and Canagliflozin (Cana) in hyperglycemic aortic rings was observed. Anti-inflammatory actions of Cana in IL-1ß-treated HUVEC and of Dapa in LPS-treated cardiofibroblast were mediated, at least partly, by AMPK activation. In isolated mouse hearts, both Empa and Cana induced vasodilation. In ischemia-reperfusion studies of the isolated heart, Empa delayed contracture development during ischemia and increased mitochondrial respiration post-ischemia. Because increased cardiac cytosolic [Ca2+] and [Na+], NHE-1 activation, elevated inflammation, impaired vasorelaxation and reduced AMPK activity are common in diabetic and failing hearts and because antagonizing these changes has been associated with improved cardiac function, the direct cardiovascular effects of SGLT2i may have large clinical impact.